Pengaruh Faktor-Faktor Kinerja Individual Terhadap Efektivitas Penggunaan Sistem Informasi Imissu - Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi, 2018)
Information systems technology used by the organization is intended to facilitate the individual in completing the task. The ease of a system and utilization in management of the system by users of the system is a determinant of the success of a system. The purpose of this study is to determine the effect of individual performance factors of accounting lecturers on the effectiveness of the use of IMISSU information systems. Population in this research is all lecturer of Accounting Department at Faculty of Economics and Business Universitas Udayana Bali. Sampling technique using purposive sampling with data collection method using questionnaire. The analysis technique used is multiple linear regression analysis. The results of this study indicate that experience, training, education, and incentives have a positive effect on the effectiveness of IMISSU use.Based on the result of research, it is suggested for Udayana University as IMISSU information system provider in order to keep improving and improving to improve organizational performance, and for IMISSU users IMISSU information system is expected to improve their ability continuously to build better performance. Keywords : Effectiveness of IMISSU Use, Work Experience, Training,Education,Incentives